Alvar Aalto in Italia : la chiesa di riola
Iglesia de Riola, 1966-1978, realizada por Alvar Aalto y Elissa Aalto.
Keywords: AALTO, ELISSA; AALTO, ALVAR; ARQUITECTURA RELIGIOSA; IGLESIAS; ITALIA; BOLOGNA; ARQUITECTURA RELIGIOSA